Trend Analysis in Lean Management: A Bibliometric Analysis - Cornejo, Vanessa María Rodríguez; Paz, Ángel Cervera; Castro, Paula Isabel Rodríguez (Journal of Ecohumanism, 2025)
Lean Management is a system comprising specific practices and techniques aimed at reducing both internal and external process variability. It encompasses a set of principles, methods, and procedures for business organisation and management. Implementing Lean Management necessitates changes in organisational culture and workforce dynamics, wherein all employees, from operator level to senior management, assume responsibilities and are empowered to make rapid decisions at all levels. This study aims to elucidate the intellectual structure of the Lean Manufacturing research field through a bibliometric analysis combining productivity and co-word analyses. This approach facilitates the identification and analysis of relationships between key topics that have significantly influenced the discipline's knowledge base. Furthermore, the evolution of keywords over time is examined, and potential future trends are identified. A search for "Lean Management" was conducted in the Web of Science (WoS), and the resulting data were processed using Bibliometrix, enabling the analysis of indices, article volume, and productivity by country, authors, and journals. Additionally, the nodes (themes) and clusters (trends) within the field of study were identified, highlighting the principal research areas.